1984
DOI: 10.1080/02626668409490918
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the level of Lake Malawi

Abstract: The level of Lake Malawi has varied widely throughout this century, and has risen dramatically in the period [1976][1977][1978][1979][1980]. The causes of the change in level have been investigated using simple numerical models based on the lake's water balance. It has been shown that the recorded changes in rainfall were sufficient to have caused the observed changes in lake level, and that man-made changes in runoff and outflow have been comparatively unimportant. Variationsde niveau du lac Malawi RESUME Le … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 3 publications
(3 reference statements)
0
30
0
Order By: Relevance
“…Similar studies on water balance by Drayton [13] in 1984 revealed a net positive change in storage between 1953 and 1974. Drayton's (1984) model was similar to Kidd's (1983) and Neuland's (1984) model, and was aimed at predicting annual maximum monthly water levels. Table 1 is a summary of the net change in storage based on previous studies.…”
Section: Review Of Water Balance Models Of Lake Malawimentioning
confidence: 48%
See 1 more Smart Citation
“…Similar studies on water balance by Drayton [13] in 1984 revealed a net positive change in storage between 1953 and 1974. Drayton's (1984) model was similar to Kidd's (1983) and Neuland's (1984) model, and was aimed at predicting annual maximum monthly water levels. Table 1 is a summary of the net change in storage based on previous studies.…”
Section: Review Of Water Balance Models Of Lake Malawimentioning
confidence: 48%
“…Using the most recent observed climate parameters of the lake, the predicted level by Neuland (1984) remains below 477 m. Probability analysis of future projected levels of the lake have shown a tendency to fall approaching gradually equilibrium of 475 m amsl [2]. Similar studies on water balance by Drayton [13] in 1984 revealed a net positive change in storage between 1953 and 1974. Drayton's (1984) model was similar to Kidd's (1983) and Neuland's (1984) model, and was aimed at predicting annual maximum monthly water levels.…”
Section: Review Of Water Balance Models Of Lake Malawimentioning
confidence: 58%
“…However, he failed due to lack of hydrological data (Dixey, 1924). Later in the years, the fear of period of no outflow by authorities greatly forced them to seriously monitor the Lake levels (Drayton, 1984). Department of Water Resources seriously embarked on collection of water levels data later in the years; however, the data collected from 1950s to somewhere around 1980s were too complex and the quality was too inconsistent.…”
Section: Data Collection and Time Series Model Descriptionmentioning
confidence: 99%
“…Kidd (1983) had similar observation in 1915 and recorded the lowest lake level of 469 m above sea level. Drayton (1984) in the 1980s reported that Lake Malawi water levels have been unstable over the years with notable events occurring in 1890s where unusual low water levels (112 m) were recorded. He further noted that the Lake water levels were near cessation of outflows for more than 20 years (from 1890s to 1935) and experienced high levels and outflows in 1970s and 1980s which caused flooding of lakeshore communities and areas immediately downstream.…”
Section: Forecastingmentioning
confidence: 99%
“…(3), with values of b close to 2 (e.g. Drayton, 1984;Piper et al, 1986). Due to operational requirements, though, there are sometimes minor departures from these rules so a separate outflow record -termed the "natural flows" here -was derived in which flows were only retained when similar to those expected from the leveloutflow relationships described by Eq.…”
Section: Case Studiesmentioning
confidence: 99%